Allele diversity for abiotic stress responsive candidate genes in chickpea reference set using gene based SNP markers - Roorkiwal, Manish; Nayak, Spurthi N.; Thudi, Mahendar; Upadhyaya, Hari D.; Brunel, Dominique; Mournet, Pierre; This, Dominique; Sharma, Prakash C.; Varshney, Rajeev K. (Frontiers in Plant Science, 2014)
Chickpea is an important food legume crop for the semi-arid regions, however, its productivity is adversely affected by various biotic and abiotic stresses. Identification of candidate genes associated with abiotic stress response will help breeding efforts aiming to enhance its productivity. With this objective, 10 abiotic stress responsive candidate genes were selected on the basis of prior knowledge of this complex trait. These 10 genes were subjected to allele specific sequencing across a chickpea reference set comprising 300 genotypes including 211 accessions of chickpea mini core collection. A total of 1.3 Mbp sequence data were generated. Multiple sequence alignment revealed 79 SNPs and 41 indels in nine genes while the CAP2 gene was found to be conserved across all the genotypes. Among ten candidate genes, the maximum number of SNPs (34) was observed in abscisic acid stress and ripening (ASR) gene including 22 transitions, 11 transversions and one tri-allelic SNP. Nucleotide diversity varied from 0.0004 to 0.0029 while PIC values ranged from 0.01 (AKIN gene) to 0.43 (CAP2 promoter). Haplotype analysis revealed that alleles were represented by more than two haplotype blocks, except alleles of the CAP2 and sucrose synthase (SuSy) gene, where only one haplotype was identified. These genes can be used for association analysis and if validated, may be useful for enhancing abiotic stress, including drought tolerance, through molecular breeding.